Assessment of Greenhouse Gas (GHG) Emissions in the Coal Mining Services Operations of PT Antareja Mahada Makmur - Deni Rahman Saputra; Probo Hardini; Hernayanti Hernayanti (Jurnal Impresi Indonesia, 2026)
The mining industry plays a substantial role in driving the increase of greenhouse gas (GHG) emissions in Indonesia, particularly through deforestation and the intensive use of fossil fuels. Consequently, evaluating GHG emissions from mining companies is essential for determining appropriate mitigation strategies. This study aims to assess the greenhouse gas emission profile within the coal mining service operations of PT Antareja Mahada Makmur. The assessment provides important insights into the environmental footprint of coal mining activities, which serve as a basis for guiding sustainable operational practices and ensuring compliance with environmental regulations. The findings indicate a notable escalation in total emissions from both mobile sources over the period from January 2025 to December 2025. Carbon dioxide (CO?) was identified as the predominant greenhouse gas emitted, especially from mobile equipment operations. These results underscore the urgency of implementing targeted mitigation measures, including enhancing energy efficiency and integrating renewable energy alternatives, to reduce the sector’s overall emission levels. Furthermore, this research offers valuable contributions in identifying emission-related challenges and proposing improvements that support corporate efforts toward achieving GHG reduction targets.